Approach to theoretical perspectives of “sexual harassment”: review and bibliometric analysis from social sciences - Cuenca-Piqueras, Cristina; Fernández-Prados, Juan Sebastián; González-Moreno, María José (Frontiers in Psychology, 2023)
The main goal of this paper is to give an overlook of the current state of sexual harassment. In order to do so, we started making a synthesis of the main theoretical approaches to explain sexual harassment, trying to group the studies into different currents that have historically analyzed this type of violence, to see whether the bibliometric analysis shows a similar presence of the different approaches. To carry out the bibliographic analysis we extracted the documents from the Scopus databases (using the keyword “sexual harassment” up to the year 2021 in the field of social sciences), where after these texts were examined with the tool VOSviewer. A description was made of the evolution of the number of articles on sexual harassment and within the areas of research and, also, the coincidences of keywords and co-authorships, highlighting the nationality and the main authors in number of citations. The results show a growth in interest in researching sexual harassment, specifically after the allegations against producer Harvey Weinstein and the #metoo movement. In the keyword analysis, there is a trend towards studies focused on the work environment and with a gender perspective. Finally, in the cluster analysis of the authorship of the texts, the results suggest the different theoretical approaches most used in the analysis of sexual harassment: socio-cultural, organizational, and multidimensional.